Illegalisierte Migration Die (De-)Konstruktion migrationsspezifischer Illegalitäten im Unionsrecht - Klarmann, Tobias (Schriften zum Migrationsrecht, 2021)
How does migration become "illegal"? Illegality cannot be observed. The work deconstructs the notion of "illegal migration" or "illegal" migrants as factual circumstances by elaborating and analysing the underlying processes, thus highlighting the constructedness as such and its specific character. The analysis concentrates on the level of EU law and ranges from migration control instruments and the phenomenon of externalisation to the involvement of third parties, the right of residence and entry bans. It is supplemented by a comprehensive examination of terminological and methodological issues.